ENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. MEDIA NUSANTARA INFORMASI BIRO JAWA TIMUR - Anindita Lakmi Prabowo (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2018)
Human resources play a very important as human as the wheels of all companyactivities. Efforts to improve the performance of the system conducted well-definedleadership and motivation to improve employee morale. This study aims to examine andanalyze the influence of transformational leadership and work motivation on the performanceof employees of PT. Media Nusantara Informasi Jawa Timur Bureau. Data were collectedused survey through questionnaires and carried out at 50 employees of PT. MNI Bureau ofJawa Timur. Data analysis in this study used SPSS version 17. The technique used ispurposive sampling and testing techniques of data used in this study include testing thevalidity of the factors, testing reliability analysis with Cronbach's alpha. Analysis of dataused multiple linear regression analysis, to test and prove the research hypotheses. Theanalysis showed that transformational leadership has a positive effect on employeeperformance and work motivation positive effect on employee performance.Keyword: Transformational leadership, motivation to work, performance of employees.